Increased utilization of electronic collections during the covid-19 pandemic: A literature review - Muhammad Fadli Suhendra; Laksmi Laksmi (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background: The Covid-19 pandemic has forced most of the people to live their personal and professional lives from home. In this condition, the use of electronic collections as a source of easy, fast, and quality information to support the learning, research, and entertainment process becomes important. Objectives: This study aims to review how the library's efforts in dealing with the increasing use of electronic resources during the Covid-19 pandemic and explore various obstacles and challenges faced by libraries in the future. Methods: The method used in this study is a literature study, namely reviewing and interpreting the latest studies that review the impact of the pandemic on increasing the use of electronic collections. From the results of a literature search, 26 scientific articles were found that were published between 2016-2021 and. Of these, 17 journal articles and 1 proceeding article were selected that were relevant to the research focus. Results: The results show that the library has empowered various electronic resources that can be accessed openly (open access). However, this increase also demands an accelerated digitization and ease of access to library services. The increase in the use of electronic resources occurs because there is a need and a major change in the behavior and attitudes of users in finding and using information. Conclusion: Increased utilization of electronic collections provides important lessons for librarians and stakeholders to become better prepared to complement and enhance new digital services, be more creative and collaborative in providing services, employ more people who are able to use new technologies to meet the needs for services and electronic collection that will continue to increase. In other words, there will be more assignments that will be requested and assigned to the library in the future.